2014
DOI: 10.3109/09540261.2014.924910
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health First Aid is an effective public health intervention for improving knowledge, attitudes, and behaviour: A meta-analysis

Abstract: Mental Health First Aid (MHFA) is a standardized, psychoeducational programme developed to empower the public to approach, support and refer individuals in distress by improving course participants' knowledge, attitudes and behaviours related to mental ill-health. The present paper aims to synthesize published evaluations of the MHFA programme in a meta-analysis to estimate its effects and potential as a public mental health awareness-increasing strategy. Fifteen relevant papers were identified through a syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
250
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 337 publications
(296 citation statements)
references
References 61 publications
22
250
0
7
Order By: Relevance
“…The California Mental Health Services Authority's (CalMHSA's) student mental health initiative included a range of PEI activities, such as training students, staff, and faculty in empirically supported approaches to recognizing and supporting individuals with mental health problems (Albright et al, 2013;Hadlaczky et al, 2014) and conducting campus trainings and social media campaigns to reduce stigma around mental health issues and to motivate students, faculty, and staff to help others (Active Minds, undated). In addition, the CCC Student Mental Health Program (SMHP), a statewide PEI initiative funded by Proposition 63 to improve student mental health across all 114 CCC campuses, awarded campus-based grants to 30 CCC campuses to expand and enhance their capacity to address the mental health PEI needs of their students, faculty, and staff.…”
Section: Key Findingsmentioning
confidence: 99%
“…The California Mental Health Services Authority's (CalMHSA's) student mental health initiative included a range of PEI activities, such as training students, staff, and faculty in empirically supported approaches to recognizing and supporting individuals with mental health problems (Albright et al, 2013;Hadlaczky et al, 2014) and conducting campus trainings and social media campaigns to reduce stigma around mental health issues and to motivate students, faculty, and staff to help others (Active Minds, undated). In addition, the CCC Student Mental Health Program (SMHP), a statewide PEI initiative funded by Proposition 63 to improve student mental health across all 114 CCC campuses, awarded campus-based grants to 30 CCC campuses to expand and enhance their capacity to address the mental health PEI needs of their students, faculty, and staff.…”
Section: Key Findingsmentioning
confidence: 99%
“…Other MHL approaches, such as Mental Health First Aid, usually target the general community, and focus on symptom identification (e.g., depression, anxiety, and schizophrenia), and awareness of help-seeking resources. While these approaches may be effective for the general public in some aspects of MHL [28], they address a limited number of MHL components when applied in the school setting, with a lack of stigma-reduction strategies and absence of positive mental health approaches; without features for potential sustainability; and with a lack of capacity building component within educational systems, especially for teacher capacity building and links with the wider community.…”
mentioning
confidence: 99%
“…In a study of stigma and help seeking, Tucker et al [21] reported that stigmatizing opinions of mental illness predicted poor help seeking attitudes for a mental disorder among individuals. Similarly in a metaanalysis, Hadlaczky et al [22] & Clement et al [23] pointed out that improving knowledge of mental illness decreased their negative opinions about mental illness; in addition leading to an improvement of attitudes towards help seeking.…”
Section: Attitudes Towards Professional Psychological Help Seeking Ammentioning
confidence: 97%